A review on recent developments in control and optimization of micro grids. (November 2022) - Ishaq, Saima; Khan, Irfan; Rahman, Syed; Hussain, Tanveer; Iqbal, Atif; Elavarasan, Rajvikram Madurai
Abstract: Modern utility grid is experiencing a transition from conservative centralized generation structure to a more distributed and decentralized structure. To achieve this transition, decentralized energy sources and loads must be seamlessly integrated and isolated from main grid structure. Realization of one such approach is termed as "Microgrid". Microgrids (MGs) are a source of clean, efficient, and an economical way to integrating renewable energy sources and loads to the main grid. Higher penetration levels of MG would lead to significant perturbations with time periods being lower than conventional dynamic responses. This may pose problems of stable operation for the entire utility grid. For addressing this problem, this paper gives an in-depth literature review on the different control structure of MGs. As control dynamics required vary significantly, depending upon the integrated source, connected loads and ratings of the MG, it is important to understand the different structures of MG. Thus, categorization of MG based on different criteria such as distributed energy resources (DERs), type of distribution systems, modes of operation, and types of communication links used are first studied. As modern control structures are layered to achieve dynamic responses at different time constants, hierarchical controls are implemented. To address this concern, different levels of hierarchical controls are also discussed along with the control strategies of integrating various renewable energy resources in MGs. Different methods of controls are analyzed and assessed in each category and the major issues faced in the current infrastructure are noted. As the grid is moving towards optimal design of microgrid structures this manuscript reviews a number of optimization techniques along with their benefits and drawbacks.